A cross sectional study of various types of acute poisoning; pharmacological management and their outcome in a tertiary care hospital - Parmar, Bhargavi D.; Thacker, Kuntal S.; Mistry, Vimesh R.; Kanani, Neeta J. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Acute poisoning is a common and life-threatening crisis, leading to serious complications and death of patients. Poisoning may be due to self-consumption, accidental exposure of chemical compounds, medications and poisonous animal bites/stings. Aim of current study was to investigate the pattern of drug utilization, poisoning agents and outcome in patients with acute poisoning treated at a tertiary care teaching hospital, Vadodara, Gujarat. Methods: This prospective cross-sectional study was done on patients of acute poisoning admitted in emergency department, SSG Hospital during August 2021-March 2022. Results: 400 patients were enrolled during the study, from which 262 (65.50%) were male and 138 (34.50%) were female. Mean age of patients was 30.30 ± 13.79 years. The commonest mode of poisoning observed was Suicidal (66.25%). The most common cause of poisoning was due to Pesticides (33.25%), followed by venomous animal exposures (30.75%). Death was recorded in 53 (13.25%) patients with highest number seen in suicidal poisoning (14.34%) compared to accidental poisonings (11.19%). Mainly, multivitamins (19.03%), Antimicrobials (16.65%), Proton Pump Inhibitors (15.85%) and Antiemetics (11.10%) were prescribed. Antidotes used were Atropine (4.81%), Pralidoxime (4.46%) and Anti-snake venom (2.80%). Median number of drugs per patient was 8; range: 2-25. Conclusions: Pattern and magnitude of poisoning are multidimensional and demand multi-sectoral approach for facing this problem. Due to high incidence of snakebites, hospital stockpiles should be regularly checked for availability of antivenom. There is a need for stringent pesticide regulation laws, counselling and training programs to reduce incidence of poisonings and deaths due to it.